1997
DOI: 10.1046/j.1365-2168.1997.02559.x
|View full text |Cite
|
Sign up to set email alerts
|

Single-visit venous ulcer assessment clinic: The first year

Abstract: In this clinic 14 per cent of leg ulcers had a significant arterial component and over half of venous ulcers may benefit from superficial venous surgery. In many ulcerated limbs, clinical assessment alone is inadequate to detect superficial reflux or previous deep vein thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 7 publications
0
34
1
Order By: Relevance
“…In the present study, in 40 patients diagnosed with chronic venous ulcers (CVU), the concomitant presence of peripheral arterial disease (PAD) was detected in 10 (25%) of them by means of ABI; this ratio was lower than that described by Nelzen (40%), 4 but higher than those reported by Anderson (24.5%), 12 Scriven (14%) 11 and Callam (21%). 13 Thus, it could be stated that the detection of concomitant chronic venous ulcers (CVU) and peripheral arterial disease (PAD) was frequent in the population studied.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…In the present study, in 40 patients diagnosed with chronic venous ulcers (CVU), the concomitant presence of peripheral arterial disease (PAD) was detected in 10 (25%) of them by means of ABI; this ratio was lower than that described by Nelzen (40%), 4 but higher than those reported by Anderson (24.5%), 12 Scriven (14%) 11 and Callam (21%). 13 Thus, it could be stated that the detection of concomitant chronic venous ulcers (CVU) and peripheral arterial disease (PAD) was frequent in the population studied.…”
Section: Resultscontrasting
confidence: 45%
“…10 Nelzen, 4 in a population study, found an ABI< 0.9 in 185 (40%) leg ulcers and Scriven, 11 in 14% of leg ulcers.…”
Section: Resultsmentioning
confidence: 99%
“…It is estimated that around half of venous leg ulcers have a surgically treatable cause and treatment of the underlying venous disease offers one way to reduce the recurrence rate. 10 The majority of patients referred with varicose veins are found to have uncomplicated truncal venous disease (CEAP C2). If a policy of not offering NHS treatment for cosmetic varicose veins is adopted, the surgical removal of superficial veins is only indicated for the subgroup of patients with functional superficial venous reflux that is a major contributor to the venous dysfunction, clinical symptoms and chronic venous ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of a wide range of etiological factors, the main causes of lower limb chronic ulcers are venous and arterial diseases; in that, 60 to 70% being caused by venous problems, the so-called venous ulcer 6,7 , and 10 to 25% by arterial insufficiency, that may coexist with venous disease (mixed ulcer). 8 In about 3.5% of patients, the cause is not identified.…”
Section: Diagnostic Managementmentioning
confidence: 99%